Aplikasi Inventory pada Byusweet Berbasis Website dengan PHP Bootstrap dan Database MySQL - Syifa Happy Januar; Mohammad Syafiuddin Usman (Melati Institute, 2023)
Byusweet is a business that is still in the pilot stage, this business is engaged in the culinary field. Every day employees have to record many incoming sales transactions, manage inventory and manage customers manually. By manually inputting data, this makes employees have to be careful in managing data, and it is possible that the data that has been managed can be lost, messy, and stained. Therefore the author makes a web-based Inventory application using PHP Bootstrap and MYSQL. The goal is to make it easier for employees to manage data and create reports. The Web-Based Inventory Application at Byusweet is an application, which makes it easy for store owners and clerks to make sales transactions and sales reports. This application is made using the PHP programming language with a MySQL database to store the data. The result of this application is that it can process information about data, such as: changing item data, adding item data, printing reports. Through this application, it is hoped that Byusweet, as previously mentioned, can be implemented and improved.